Dimensions of diversity in modern spring bread wheat in developing countries from 1965 - Smale, Melinda; Reynolds, M. P.; Warburton, Marilyn L.; Skovmand, Bent; Trethowan. R. M.; Singh, R. P.; Ortiz-Monasterio, J. Ivan; Crossa, J. (Wiley, 2002)
Diverse and varied crop genetic resources are necessary (though not sufficient) for adequate food production in a rapidly changing world. Since the scientific community first raised public concern several decades ago, modern cultivars have been viewed as the cause of declining diversity in the world's crop genetic resources. This paper tests the hypothesis of increasing genetic uniformity in modern spring bread wheat (Triticum aestivum L.) cultivars from 1965, a year which marks the release of some of the first modern semidwarf cultivars carrying Rht1 and Rht2 genes in the developing world. Results from previously published studies are summarized. Preliminary molecular analyses, and new analyses of cultivar numbers, areas, ages, and genealogies are presented. An estimated 77% of the spring bread wheat area in the developing world today is sown to CIMMYT‐related wheats, but this does not imply that they are genetically uniform. The hypothesis of increasing genetic uniformity is tested by assessing changes in the diversity of leading progenitors over three decades, in terms of several dimensions of diversity. Latent dimensions include genetic distance and genealogies. Apparent dimensions include performance with respect to yield potential, maintenance and stability across management (input use), and growing environments. The data are not consistent with the view that the genetic diversity of modern semidwarf wheat grown in the developing world has decreased over time. Moreover, since national programs in developing countries cross CIMMYT lines with their own materials before releasing them, the genetic diversity in their cultivars is at least as great as that present among CIMMYT lines.